Leishmania braziliensis Subverts Necroptosis by Modulating RIPK3 Expression - Luz, Nivea F.; Khouri, Ricardo; Van Weyenbergh, Johan; Zanette, Dalila L.; Fiuza, Paloma P.; Noronha, Almerio; Barral, Aldina; Boaventura, Viviane S.; Prates, Deboraci B.; Chan, Francis Ka-Ming; Andrade, Bruno B.; Borges, Valeria M. (Frontiers in Microbiology, 2018)
Leishmania braziliensis infection causes skin ulcers, typically found in localized cutaneous leishmaniasis (LCL). This tissue pathology associates with different modalities of cell necrosis, which are subverted by the parasite as a survival strategy. Herein we examined the participation of necroptosis, a specific form of programmed necrosis, in LCL lesions and found reduced RIPK3 and PGAM5 gene expression compared to normal skin. Assays using infected macrophages demonstrated that the parasite deactivates both RIPK3 and MLKL expression and that these molecules are important to control the intracellular L. braziliensis replication. Thus, LCL-related necroptosis may be targeted to control infection and disease immunopathology.